(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
The present study explains the levels of proteins and enzymes like proteases and amylases associated with the breakdown of proteins and carbohydrates during various stages (0 day to 15th day) of seed germination of Sterculia urens Roxb.. Maximum protease activity (1.12 units/mg of protein) and amylase activity was observed on 12thday of seed germination (34 units/mg of protein) and decreased thereafter. Highest protein content was observed at initial stage of seed germination and decreased thereafter. Increased proteolytic activity and amylase activity proportionately increases free amino acid content and sugars that promotes the seedlings growth and development. Bangladesh J. Sci. Ind. Res.55(2), 107-112, 2020